Implementation of management functions of MADASI Islamic da'wah in forming religious characters in Muslim society - Zuhriah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this paper is to determine the implementation of management functions by the Islamic DA'WAH organization, namely 'Majelis Da'wah Syiar Islam (MADASI) in shaping the character of the religious soul of the community. The research method used is qualitative research. Data collection techniques were carried out by means of observation and interviews. The informants in this study were members of the MADASI organization that is plantation employees and retirees. The technique of determining the informant uses purposive sampling. Meanwhile, the data analysis was done qualitatively. Data analysis in this study was carried out through three activities which were: occur simultaneously, namely data reduction, data presentation, and withdrawal conclusion or verification. The results of this study found that the Role of the Organization of the Islamic Propagation Council (MADASI) of the Upper Oil Palm Plantation in realizing very good management functions, among others. The Islamic Propagation Council (MADASI) Kebun Sawit Hulu uses Islamic concepts in carrying out all plans, both monthly and annual plans. The process of organizing the Islamic Propagation Council (MADASI) of the Upstream Oil Palm Plantation is very good and neatly arranged. This is supported and protected by the Manager of the South and North Hulu and North Palm Plantation. The direction given by the head of the Islamic Propagation Council (MADASI) of the Upper Palm Oil Plantation to all its management was carried out well and constantly reminded the administrators of the work they had received. The activities carried out went well, and also the supervision of the head of the field of their respective work was in accordance with their place. This can run effectively due to good communication between the chairman and also all administrators of the Islamic Propagation Council (MADASI) Hulu Palm Plantation. This research implies that the da'wah planning process is carried out MADASI assembly can improve religion in routine recitation activities and religious tourism.